2012
DOI: 10.1080/10803548.2012.11076937
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects Associated With Shift Work in 12-Hour Shift Schedule Among Iranian Petrochemical Employees

Abstract: Introduction. The main purposes of this study were to investigate shift-work-related health problems inshift work 12-hour shift schedule extended work shift health problems petrochemical industry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 23 publications
1
23
0
1
Order By: Relevance
“…Choobineh et al. () also reported similar findings after their study on petrochemical employees in Iran. The findings of this study can be used by welding equipment manufacturers for designing tools based on ergonomic principles.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Choobineh et al. () also reported similar findings after their study on petrochemical employees in Iran. The findings of this study can be used by welding equipment manufacturers for designing tools based on ergonomic principles.…”
Section: Discussionsupporting
confidence: 64%
“…A set of employment factors, such as occupation, physical workload, location of work, hazards in work system, work‐rest cycle, activity, shift of working, manual material handling, job responsibility, job performance, working hours, apprenticeship training, and type of employment, that influence MSD discomfort/pain were reported in the literature in recent years (Attarchi, Raesis, Namvar, & Golabadi, ; Choobineh, Soltanzadeh, Tabatabace, Jahangiri, & Kavaji, ; Davies, Kemp, Frostick, & McElwaine, ; Ferguson, McNally, & Booth, , ; Frank, ; Hanecke, Tiedemann, Nachreiner, & Grzech, ; Haslam et al., ; Johnson & Sharit, ; Josephine, Joost, Vander, Theo, & Hof, ; Khanzode, Maiti, & Ray, ; Kumar & Dharanipriya, ; Leigh, Mulder, Want, Farnsworth, & Morgan, ; Levin, Oler, & Whiteside, ; Maiti & Bhattacherjee, ; Maiti, Bhattacherjee, & Bangdiwala, ; Maiti, Chatterjee, & Bandiwala, ; Niklas, ; Quinlan et al., ; Torner, Zetterberg, Anden, Hanson, & Lindell, ).…”
Section: Methodsmentioning
confidence: 99%
“…Also, some other studies conducted by Demerouti [65] and that of Janssen [66] showed that the circadian rhythm disorder was affected by shift-work and night shift-work and caused MSDs in low back region of nursing personnel. Choobineh in his cross-sectional study also reported that the prevalence of LBP can be due to various risk factors such as shift-work [67]. Meanwhile, in a study by Eriksen, night shift-work was recorded as one of the most important factors for the Nurse's LBP [68].…”
Section: Discussionmentioning
confidence: 96%
“…Although in the present study the prevalence of LBDs was higher among shift workers (64%) than among day workers (51%) (p = .001), after adjustment for confounding factors, the association was insignificant. A study on petrochemical employees showed that prevalence of health problems such as MSDs in shift workers was higher than in day workers [33]. According to Eriksen, Bruusgaard and Knardhal, shift working, heavy lifting, moderating work demands, losing support in a workplace, working in nursing home are risk factors for low back pain among nurses' aides [34].…”
Section: Discussionmentioning
confidence: 99%